Manitoo Mazina'igan: Anishinaabe legal analysis of Treaty No. 3 - Seymour, Janine R. (2016)
Historical Treaties entered into with Indigenous peoples are often a source of conflict. This conflict is connected to treaty implementation, which tends to be at the sole discretion of the domestic jurisdiction. Accordingly, a one-sided interpretation of a two-sided agreement is a problematic approach. This thesis will explore key concepts of Indigenous law, in relation to the historical Treaties made with the Crown. Particular emphasis will be on the Anishinaabe in Treaty No. 3 in Turtle Island, the State now known as Canada. Indigenous law will be grounded in widely accepted international law principles, which may allow for further insight by the Treaty partners. Through grounding the Indigenous perspective of the true spirit and original intent of the Treaties, explanation can be drawn out and further understanding between the parties will occur. Mutual understanding, along with respect, is part of the foundation to the reconciliation process of the relationship between Indigenous and non-Indigenous peoples. February 2016